NGO insecurity in high-risk conflict zones: the politicization of aid and its impact on “humanitarian space” - Mitchell, John "David" F. (Kansas State University, 2016)
Attacks against nongovernmental organizations (NGOs) in high-risk conflict zones have increased exponentially over the last two decades. However, the few existing empirical studies on NGO insecurity have tended to focus on external factors influencing attacks, with little attention paid to the actions of aid workers themselves. To fill this gap, this dissertation theorizes that aid workers may have contributed to their own insecurity by engaging in greater political action. Both quantitative and qualitative methods are used to assess the impact of political activity by NGOs on the insecurity of aid workers. The quantitative analyses test the theory at two levels. The first is a large-N country-level analysis of 117 nations from 1999 to 2015 using panel corrected standard errors. The second is a subnational-level statistical analysis of four case studies: Afghanistan, Iraq, Somalia, and Colombia from 2000 to 2014. Both the country- and provincial- level analyses show that the magnitude of aid tends to be a significant determinant of aid worker security. The qualitative methods of “structured-focused comparison” and “process tracing” are used to analyze the four cases. Results show that aid workers are most likely to be victims of politically-motivated attacks while in-transit. Consistent with the quantitative findings, it is speculated that if workers are engaged in a large-scale project over an extended period of time, attackers will be able to monitor their daily activities and routines closely, making it easier to orchestrate a successful ambush. Furthermore, the analysis reveals that political statements made by NGOs—regardless of their sectors of activity—have increased insecurity for the broader aid community. These results dispel the myth that humanitarian activity has historically been independent, impartial, and neutral. Several NGOs have relied on this false assumption for security, believing that adherence to core principles has contributed to “humanitarian space.” The results also dispel the popular NGO assumption that targeted attacks are not official tactics of organized militants, but rather the result of criminality or mistaken identity. In fact, the overwhelming majority of aid workers attacked in high-risk conflict zones have been targeted by political actors.
Keywords: Aid worker security; Humanitarianism; Human rights; International development; Nongovernmental organizations; Civilian casualties